MUHAMMADIYAH DALAM KACAMATA NAHDLATUL ULAMA - Sayida Nafisa Azmi; Ashif Az Zafi (Universitas Muhammadiyah Surakarta, 2021)
This report aims to determine the organization of Muhammadiyah in the view of the Nahdlatul Ulama Organization (NU). The issue of this report is how NU's view of Muhammadiyah is. The method used is the literacy method or library. The result of this report is that there is a long-term rise in relations, while both seem very familiar, but at other times a distant kinship. The current awareness that many of the issues of Muslims to be solved together should be a common thought material for both of them working together, such as quality issues of human resources, health, and economic welfare. This cooperation will increase the capacity of building Muslims in Indonesia on the issues. The closeness that arises because of involvement in these joint works will bring about a deeper personal and organizational relationship between Muhammadiyah and NU. This will improve one another's problems in looking at a problem or do a tabayyun when there is a thing that needs to be explained.